Electrical impedance tomography for meat marbling prediction - Ulum, Mokhamad Fakhrul; Cristovao, Adelaide Jose Pereira; Wijaya, Surya Kusuma; Pamungkas, Fitra Aji; Jakaria, Jakaria (ARSHI Veterinary Letters, 2024)
Electrical Impedance Tomography (EIT) is a promising noninvasive technology for predicting meat quality traits, such as marbling in beef. Marbling, characterized by intramuscular fat, significantly influences beef quality by enhancing flavor, tenderness, and juiciness. This review evaluated the application of EIT in meat quality control, highlighting its ability to measure changes in conductivity to assess marbling and other quality attributes. Integrating EIT with machine-learning techniques further refines its predictive capabilities. Although EIT provides real-time, noninvasive assessments with lower costs, challenges like lower signal-to-noise ratios and complex algorithm requirements persist. Future directions include the integration of EIT with modern packaging systems and automation tools to enhance meat quality monitoring and industrial efficiency.